The Use of LIDAR Technology in Architectural Offices (European Journal of Engineering Science and Technology, 2019)
Together with the developing technology, robotic systems are used in many areas such as defence technologies, manufacturing industry, search and rescue. The integration of these systems into different areas decreases the need for manpower and has a positive effect on cost. From the past to the present, architectural structures have been made by man-power. On the other hand, the effects of robotics systems in the construction have been observed in recent years. Especially with the usage of 3-dimensional printers and building materials, the construction time is shortened and large financial gains have begun. The use of technology is also seen in the field of interior architecture. By means of machine learning and deep learning algorithms, different furniture and home decorations have been selected according to the dimensions of the room. For example, the algorithm chooses the highest accuracy to have the best visualization and usage area of ??the furniture to be selected considering the room size and shape. In this paper, it is aimed to map the interior decoration environment through the LIDAR. It is clear that it is difficult to take measurements and prepare plans with traditional methods. The LIDAR, an advanced laser distance measuring sensor, measures the distance as a result of returning the beam spread by itself. The time of LIDAR measurement can be as short as 1 minute. Although it is not a millimeter, it is possible to map draft plans and space sizes in a very short time. Using the Hector Mapping algorithm, a house mapped with LIDAR was found to give high results in terms of accuracy, while it was found to be a great gain in terms of time. The house was fully mapped and the reference door width was entered and the place was made ready for interior decoration.